Metode Muraja’ah dalam Menghafal Al-Qur`An di Pondok Pesantren Al-Mubarok Tahtul Yaman Kota Jambi - Yuliani Rahmi (INNOVATIO: Journal for Religious Innovation Studies, 2019)
This study aims to find out how the process of applying the muraja’ah method in memorizing al-Qur`an at al-Mubarak Islamic Boarding School. The study uses qualitative research, with data collection through documentation, interviews, observation and questionnaires. Key informants are Kyai Pondok Pesantren, Deputy Head of Curriculum, Ustadz/ Ustadzah, Santriwan/ Santriwati. This study found that the effectiveness of the Muraja'ah Method in Memorizing al-Qur`an in al-Mubarok Islamic Boarding School in Tahtul Yaman Village, Pelayangan District of Jambi City still experiences obstacles in memorizing activities, the existing constraints: 1) Lack of motivation santri in muraja'ah hafalan al-Qur`an, 2) Lack of time management and lack of discipline, and 3) Environmental conditions.